PENGARUH INTERAKSI PARASOSIAL DI INSTAGRAM TASYA FARASYA TERHADAP PERILAKU IMPULSE BUYING PRODUK "MOTHER OF PEARL" - RAHMI ANISA GUSIKA PUTRI, (2024)
Impulse Buying behavior has grown significantly with today's technological developments. Impulse Buying or Impulsive Buying is an unplanned, unmanaged or spontaneous behavior when buying a product. This behavior often occurs in the younger generation, especially Gen Z, who are exposed to a lot of media, especially influencers they like. One of the Influencers in the Beauty sector is @tasyafarasya. This Beauty Influencer also uses Instagram to share her daily activities, interact with her followers, and post content about her own make-up product, namely "Mother of Pearl", which sold out within 8 hours of its first launch, this phenomenon is the background for this research. This research aims to determine the magnitude of the influence of parasocial interactions on @tasyafarasya Instagram on Impulse Buying behavior of "Mother of Pearl" product and the benefit of this research is to prove the Elaboration Likelihood Model (ELM) which states that individuals will produce changes in attitude if given a persuasive message. This research uses quantitative methods with an explanatory research type, and uses data collection techniques in the form of questionnaires. Based on the results of the correlation calculation test, a value of 0.553 was obtained. These results show that Parasocial Interaction on Instagram @tasyafarasya has a strong influence on Impulse Buying of "Mother of Pearl" Products. Also found was the influence of the Parasocial Interaction variable onImpulse Buying amounting to 69% through the coefficient of determination test. Meanwhile, the hypothesis test obtained the results that Ho was rejected and Ha was accepted with a significance value of 0.001.